Suspended Sediment Concentration and Stream Discharge Relationship During Storm Events in Tributaries of Smaquli Stream, Erbil, Iraq - M. Gardi , Lookman M.; Al-Shamma’a, Ayser Mohammed (Iraqi Journal of Science, 2022)
The primary objective of this study is to monitor and collect data from the maintributaries of Smaquli stream during rainfall storm events, which can be used toestablish relationship between suspended sediment concentration and discharge. TheSmaquli catchment is divided into two sub-catchments namely Sarwchawa andKrosh with areas of 80.64 and 34.82 km2 respectively. Jali dam is built at watershedoutlet. Rainfall, stream discharge, and suspended sediment concentration aremonitored during ten rainfall storms in the water years (2012-2013) and (2013-2014). Analysis of the data from the two sampling sites, shows two differentresponses of suspended sediment concentrations. The Krosh sub-catchment reactsrapidly to rainfall storms and the same behavior is shown in the suspended sedimentthat is resulted seven single and three double-peaked graphs. On the other hand, thereaction of Sarwchawa sub-catchment was slower. Moreover, analysis of cumulativeflow and suspended sediment showed the Krosh sub-catchment ranks almost equallyas one of the flow and sediment contributors to the Smaquli stream, in spite of thearea difference between Sarwchawa and Krosh sub-catchments. The peak streamflows are highly correlated with total and peak suspended sediments at Krosh stationhaving correlation coefficients of (R=0.96 and 0.84) respectively. In contrast, atSarwchawa sub-catchment, the peak stream flow was weakly correlated with peaksuspended sediment (R=0.47). To reduce sedimentation, this study suggestschanging the land use practices for example types of crops and frequent planting andless grazing of sheep and goats.